Human MLH1/3 variants causing aneuploidy, pregnancy loss, and premature reproductive aging - Priti Singh (Nature Portfolio, 2021)
Proper meiotic chromosome segregation requires mismatch repair genes MLH1 and MLH3, of which variants occur in the human population. Here, the authors use computational predictions and yeast assays to select human MLH1/3 variants for modelling in mice, observing reproductive defects from abnormal levels of crossing over.